The elementary school teachers' ability in the length measurement - Julie, Hongki (Journal of physics. Conference series, 2017)
The purpose of this study was to describe the elementary school teachers' mathematical ability (1) to develop students' activities which constructed longer than, shorter than, and as long as concepts, (2) to develop students' activities which constructed standard unit on the length measurement, and (3) to develop a problem which used by student to construct why a conversion activity on the unit of the length was useful in the daily life after they have participated in the Realistic Mathematics Education (RME) workshops. Curry and Outhread said if teachers knew more about the growth of students' conceptual understanding of the length, they would be better able to teach that topic [4]. Therefore, in the workshop, teachers were asked to learn more on the stages of the measurement teaching and learning process and why each stage was important. This capability was described by the results of a test which was content of four problems given to teachers after they have attended the workshop. Research subjects in this study were 14 elementary school teachers at Yogyakarta. The results of the study were as follows: (1) only four of 14 teachers who had the first ability; (2) all teachers had the second ability; and (3) all the teachers did not have the third ability.